WORD FORMATION PROCESS ON AVIATION TERMS IN ENGLISH FOR AVIATION BOOK - Zakri Azis (English Language and Literature, 2018)
In today’s advanced technology, the needs of word formation increase because more and more terms to support such technology advancement were invented. This also happens to aviation terms that also introduces several new terms that might be still strange to the public. Therefore, it is necessary to conduct a study on word formation of aviation terms in order to facilitate the public understanding of aviation terms. The purpose of this study is to analyze the types of word formation of aviation terms in English for Aviation Book published by Oxford. This study used a descriptive qualitative method. The data were the words contained in the listening transcript of the book. The data were analyzed based on the theories of word formation proposed by Bryson (1990), O’Grady et al. (1997), Pena (2010), Plag (2002) and Yule (2010). Based on the data analysis, it was found that there are 12 out of 17 types of word formation proposed by aforementioned experts. They are (1) Derivation, (2) Inflection, (3) Coinage, (4) Conversion, (5) Acronym, (6) Initialism, (7) Compounding, (8) Back-formation, (9) Internal Change, (10) Suppletion, (11) Onomatopoeia, and (12) Multiple Processes. Among the 12 types of word formation found, the type of word formation most frequently used in aviation terms is inflection with the frequency of 112 data (31,20%). This finding shows that words used in aviation terms are sensitive to the grammatical needs of the words in the structure.